The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.14417/ap.1645
|View full text |Cite
|
Sign up to set email alerts
|

Quality of sibling relationship and parental differential treatment in a sample of Portuguese adolescents

Abstract: Os irmãos são extremamente importantes na vida do adolescente. Com este estudo tivemos por objetivo explorar de que modo estão relacionados a vinculação entre irmãos, o tratamento parental diferenciado e o uso de táticas resolução de conflito no relacionamento entre irmãos. Numa amostra de 192 adolescentes portugueses, 64.6% do sexo feminino, com idades compreendidas entre os 11 e os 16 anos, aplicou-se o Inventário de Vinculação na Adolescência (versão irmãos), as Escalas de Táticas do Conflito Revisadas (ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…(Table 2 & 3). These findings are consistent with the previous findings that indicate that maternal and paternal affection is positively correlated with sibling warmth and negatively with conflict and rivalry, and maternal and paternal control is positively related to sibling conflict and rivalry and negatively to sibling warmth (Relva et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…(Table 2 & 3). These findings are consistent with the previous findings that indicate that maternal and paternal affection is positively correlated with sibling warmth and negatively with conflict and rivalry, and maternal and paternal control is positively related to sibling conflict and rivalry and negatively to sibling warmth (Relva et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Meningomyelocele is one of the most common congenital malformations (Adzick, 2010; Copp et al, 2015; Şeker Abanoz et al, 2020). The family is the most immediate environment for the child's growth and socialisation (Ljubičić et al, 2022), and the sibling relationship is the longest in human life (Relva et al, 2019). Our results reinforce the relevance of knowing the factors that influence the three dimensions studied, and of further research in these fields of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, Menesini et al found in a sample of 195 children with ages ranging between 10 and 12 years that girls were more at risk of bullying from their older brothers, who are more dominant in sibling relationships, when compared with older sisters, who tend to be more responsible and protective. More recently, Relva, Alarcão, Fernandes, and Graham-Bermann (2019) in a study with 192 adolescents with ages between 12 and 19 years explored the association between sibling attachment, sibling abuse, and parental deferential treatment, concluded that perpetration of physical aggression was positively associated with sibling distance.…”
Section: Quality Of Sibling Relationshipmentioning
confidence: 99%